Smokeless Tobacco: Pattern and Awareness in a Rural Area of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Smokeless tobacco consumption has contributed nothing except diseases, disability and death. But assessment of awareness and knowledge regarding its use has less been studied to the extent as that of smoking. The study was undertaken to assess the pattern of use and awareness of smokeless tobacco among rural community.Materials and methods: This descriptive cross-sectional study was conducted among 310 respondents selected through systemic sampling method, aged 18 years, residing at least for 10 years in Noakhali district in Bangladesh. This study was conducted from May to November 2013. Data were collected with a pretested questionnaire through face-to-face interview. Results: Smokeless Tobacco (SLT) use was prevalent among 45.8% of respondents. Higher proportion of females than males used SLT. Zarda was the common form in more than half of the users. Among daily users, self-interest was the main factor for initiation and mean age of starting was 35 years.  Per day frequency of SLT use for 1-8 times was in two-thirds of the daily users. Most of the respondents knew that SLT is injurious to health. About two-thirds of them mentioned SLT as addictive. More than one-thirds of the respondents had knowledge that smoking is more injurious than SLT. However, 30% of the respondents knew that both smoking and SLT were equally addictive. Excluding the former users, majority of the respondents knew that SLT might be quitted.  Conclusion: Multistage effective behavioral change intervention programs are the preferable way to overcome this lifestyle-related health problem.JCMCTA 2022 ; 33 (1) : 166-172